The privacy paradigm : An overview of privacy in Business Analytics and Big Data - Chaves, A. (2021)
In this New Age where information has an indispensable value for companies and data mining technologies are growing in the area of Information Technology, privacy remains a sensitive issue in the approach to the exploitation of the large volume of data generated and processed by companies. The way data is collected, handled and destined is not yet clearly defined and has been the subject of constant debate by several areas of activity. This literature review gives an overview of privacy in the era of Business Analytics and Big Data in different timelines, the opportunities and challenges faced, aiming to broaden discussions on a subject that deserves extreme attention and aims to show that, despite measures for data protection have been created, there is still a need to discuss the subject among the different parties involved in the process to achieve a positive ideal for both users and companies.